Understanding international migration: Evidence from a new dataset of bilateral stocks (1960-2000) - Joan Llull (SERIEs - Journal of the Spanish Economic Association, 2016)
In this paper I present a new database of bilateral migrant stocks and I provide newevidence on the determinants of international migration. The newCensusbased data are obtained from National Statistical Offices of 24 OECD countries, and they cover the total stock of immigrants in each destination country for 1960-2000, including 188 countries of origin, sometimes in grouped categories. For each census, I keep grouped categories in a raw manner, without making imputations to specific origin countries. In the empirical analysis, I give an explicit treatment to these grouped categories. Results present strong evidence of heterogeneous effects of income gains on migration prospects depending on distance. For example, a 1000 increase in US income per capita increases the stock of Mexican immigrants in the country by a percentage 2.6 times larger than the percentage increase in the stock of Chinese (8 vs. 3.1 %).
Keywords: F22; J61; O15; 330; International migration; Data collection; Grouped data